Do multinational banks create or destroy shareholder value? A cross-country analysis - Gulamhussen, M. A.; Pinheiro, C.; Pozzolo, A. F. (Financial Markets Institutions and Instruments, 2017)
We question whether the international diversification of multinational banks creates or destroys shareholder value. Based on a sample of 384 listed banks from 56 countries we provide new and robust evidence that bank cross-border activities create shareholder value, as shown by an economically and statistically significant premium for international diversification. Our results are confirmed controlling for bank fixed effects, time-varying bank characteristics, reverse causality, functional diversification, and instrumenting for the choice to expand abroad. The increase in shareholder value is slightly larger for banks in the middle range of international diversification and in the case of expansion towards less developed countries.